2017
DOI: 10.1002/cncr.30788
|View full text |Cite
|
Sign up to set email alerts
|

The association between complications and quality of life after mastectomy and breast reconstruction for breast cancer

Abstract: There is a strong case for prospectively collecting flap-complication rates at the surgeon and surgical unit level and for allowing patients to access these data when they make choices about their breast cancer surgery. Cancer 2017;123:3460-7. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
4
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 12 publications
1
42
4
6
Order By: Relevance
“…Nine studies out of 20 (45%) reported results favoring autologous procedures for psychosocial and sexual well‐being . Some studies also differentiated between different types of autologous procedures, favoring DIEP flaps over TRAM for psychosocial and physical well‐being on the abdomen .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies out of 20 (45%) reported results favoring autologous procedures for psychosocial and sexual well‐being . Some studies also differentiated between different types of autologous procedures, favoring DIEP flaps over TRAM for psychosocial and physical well‐being on the abdomen .…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, four studies out of 11 (36%) suggested that complications had a significant impact on physical, emotional, and sexual well‐being . Menez et al reported that major complications (vs minor) were associated with lower psychosocial, emotional, and sexual well‐being, while Winters et al found that early complications (vs later) were associated with lower overall quality of life.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations